Salsoline derivatives, genistein, semisynthetic derivative of kojic acid, and naringenin as inhibitors of A42R profilin-like protein of monkeypox virus: in silico studies - Chebaibi, Mohamed; Bourhia, Mohammed; Amrati, Fatima ez-zahra; Slighoua, Meryem; Mssillou, Ibrahim; Aboul-Soud, Mourad A. M.; Khalid, Asaad; Hassani, Rym; Bousta, Dalila; Achour, Sanae; Benhida, Rachid; Daoud, Rachid (Frontiers in Chemistry, 2024)
Monkeypox virus (MPV) infection has developed into a re-emerging disease, and despite the potential of tecovirimat and cidofovir drugs, there is currently no conclusive treatment. The treatment’s effectiveness and cost challenges motivate us to use In Silico approaches to seek natural compounds as candidate antiviral inhibitors. Using Maestro 11.5 in Schrodinger suite 2018, available natural molecules with validated chemical structures collected from Eximed Laboratory were subjected to molecular docking and ADMET analysis against the highly conserved A42R Profilin-like Protein of Monkeypox Virus Zaire-96-I-16 (PDB: 4QWO) with resolution of 1.52 Å solved 3D structure. Compared to the FDA-approved Tecovirimat, molecular docking revealed that Salsoline derivatives, Genistein, Semisynthetic derivative of kojic acid, and Naringenin had strengthened affinity (−8.9 to −10 kcal/mol) to 4QWO, and the molecular dynamic’s simulation confirmed their high binding stability. In support of these results, the hydrogen bond analysis indicated that the Salsoline derivative had the most robust interaction with the binding pockets of 4QWO among the four molecules. Moreover, the comparative free energy analyses using MM-PBSA revealed an average binding free energy of the complexes of Salsoline derivative, Genistein, Semisynthetic derivative of kojic acid, Naringenin, of −106.418, −46.808, −50.770, and −63.319 kJ/mol, respectively which are lower than −33.855 kJ/mol of the Tecovirimat complex. Interestingly, these results and the ADMET predictions suggest that the four compounds are promising inhibitors of 4QWO, which agrees with previous results showing their antiviral activities against other viruses.